2021
DOI: 10.1186/s12934-021-01692-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying carbohydrate-active enzymes of Cutaneotrichosporon oleaginosus using systems biology

Abstract: Background The oleaginous yeast Cutaneotrichosporon oleaginosus represents one of the most promising microbial platforms for resource-efficient and scalable lipid production, with the capacity to accept a wide range of carbohydrates encapsulated in complex biomass waste or lignocellulosic hydrolysates. Currently, data related to molecular aspects of the metabolic utilisation of oligomeric carbohydrates are sparse. In addition, comprehensive proteomic information for C. oleaginosus focusing on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 122 publications
0
8
0
Order By: Relevance
“…In general, it has been shown that the uptake of glucose and xylose shows very similar growth rates and lipid production with C. oleaginosus . Fatty acid biosynthesis in this nonconventional yeast is carried out by the fatty acid synthase complex (FAS) which requires acetyl-CoA .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, it has been shown that the uptake of glucose and xylose shows very similar growth rates and lipid production with C. oleaginosus . Fatty acid biosynthesis in this nonconventional yeast is carried out by the fatty acid synthase complex (FAS) which requires acetyl-CoA .…”
Section: Resultsmentioning
confidence: 99%
“…In general, it has been shown that the uptake of glucose and xylose shows very similar growth rates and lipid production with C. oleaginosus. 32 Fatty acid biosynthesis in this nonconventional yeast is carried out by the fatty acid synthase complex (FAS) which requires acetyl-CoA. 33 Glucose mainly channels into the glycolysis and pentose phosphate pathways, while xylose can be metabolized both by the phosphoketolase and pentose phosphate pathways.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Proteins were extracted and precipitated with Protein Extraction Reagent Type 4 (Sigma-Aldrich, St. Louis, MO, USA) (1:3, v / v ) and 20% trichloric acid ( v / v ), followed by in-gel digestion with trypsin. Peptides were analyzed using LC-MS/MS analysis with a timsTOF Pro mass spectrometer equipped with a NanoElute LC System (Bruker Daltonik GmbH, Bremen, Germany) on an Aurora column (250 × 0.075 mm, 1.6 μm; IonOpticks, Hanover St., Rozelle, NSW, Australia) [ 21 , 22 ]. For every condition, three biological and two technical replicates were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Its superiority over other oleaginous microorganisms in having high triglyceride (TAG) content, substrate flexibility, and rapid growth rate has made this yeast a prime candidate for oleochemical production [5][6][7]. To date, C. oleaginosus has displayed the highest carbon source flexibility linked with high de-novo oil productivity and yield of any oleaginous yeast strain [7][8][9][10][11][12][13]. Moreover, compared to other yeasts, C. oleaginosus is highly resistant to fermentation inhibitors (including weak organic acids e.g.…”
Section: Introductionmentioning
confidence: 99%